Eficacia del uso sistémico del metronidazol y la azitromicina como coadyuvantes en la terapia periodontal no quirúrgica Una revisión narrativa. (2023)
Objective: The objective of the following investigation is to analyze the clinical differences in non-surgical periodontal therapy, with the use of azithromycin and metronidazole as coadjuvants in the treatment. Methodology: Methodology: A search was carried out in several databases, with the following keywords periodontics, azithromycin, metronidazole, therapy, treatment, non-surgical. In which 2,050 articles were found, where 161 articles were included and 116 articles were excluded by titles, in which the clinical differences of the antibiotics azithromycin and metronidazole were reviewed as an adjuvant in non-surgical periodontal therapy. Clinical outcomes (changes in probing depth and insertion level) were divided.